1987
DOI: 10.1021/jo00388a032
|View full text |Cite
|
Sign up to set email alerts
|

Participation by ether oxygen (RO-3) in the hydrolysis of sulfonate esters of 2-methoxyethanol and 2-methoxy-2-methyl-1-propanol. Implications regarding the nonlinear ethanol-trifluoroethanol plot for mustard chlorohydrin

Abstract: The lack of scrambling with deuterium-labeled reactants, a nonlinear ethanol-trifluoroethanol plot, and rate acceleration by added thiourea are used to show that sulfonate esters of methoxyethanol (MeOCH2CH2OH) undergo solvent-assisted displacement in a variety of solvents; neighboring group participation by ether oxygen (RO-3 participation) does not occur. This conclusion is in accord with predictions of rate based on the Taft treatment of substituent effects. On the other hand, the branched derivative MeOCMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…These nucleophilic displacements probably proceed by an S N 2 mechanism, even though S N 2 displacements of halides and tosylates in neopentyl derivatives are known to occur slowly and mechanisms involving single electron transfer (S RN 1) are often considered for displacement of neopentyl halides, particularly iodides. , It is probable that S N 2 displacements in pentaerythritol systems are faster than those in neopentyl systems because of neighboring group participation as shown in Scheme . Although participation by oxygen through four-membered-ring intermediates does not normally provide significant rate enhancement, when branching on the intervening atoms is present, significant rate enhancements have been observed. , Dale and Fredriksen suggested that displacements of bromides by alkoxides from 2-bromo-2-methyl-1,3-dibromopropane proceed via four-membered-ring bromonium ion intermediates . We believe that the iodide displacements here follow the S N 2 mechanism both because neighboring group participation is possible and also because the dependency of ease of reaction on the steric bulk of the nucleophile fits what is expected for an S N 2 mechanism.…”
Section: Resultsmentioning
confidence: 70%
“…These nucleophilic displacements probably proceed by an S N 2 mechanism, even though S N 2 displacements of halides and tosylates in neopentyl derivatives are known to occur slowly and mechanisms involving single electron transfer (S RN 1) are often considered for displacement of neopentyl halides, particularly iodides. , It is probable that S N 2 displacements in pentaerythritol systems are faster than those in neopentyl systems because of neighboring group participation as shown in Scheme . Although participation by oxygen through four-membered-ring intermediates does not normally provide significant rate enhancement, when branching on the intervening atoms is present, significant rate enhancements have been observed. , Dale and Fredriksen suggested that displacements of bromides by alkoxides from 2-bromo-2-methyl-1,3-dibromopropane proceed via four-membered-ring bromonium ion intermediates . We believe that the iodide displacements here follow the S N 2 mechanism both because neighboring group participation is possible and also because the dependency of ease of reaction on the steric bulk of the nucleophile fits what is expected for an S N 2 mechanism.…”
Section: Resultsmentioning
confidence: 70%
“…The topic of mustard (bis(2-chloroethyl)sulfide) hydrolysis reaches back to the work of Hopkins in 1919 . In subsequent years numerous publications exploring this topic have been published. In spite of all this work, the mechanism of mustard hydrolysis remains elusive. Last year alone, another 105 publications on facets of mustard chemistry were added to ChemAbstracts, and current world events demonstrate the continued relevance of mustard.…”
Section: Introductionmentioning
confidence: 99%
“…2-Chloroethyl ethyl sulfide yielded only two sulfonium salts and one organic product, greatly simplifying the identification and monitoring of the reaction. Previous work by McManus and co-workers , using 2-chloroethyl ethyl sulfide or 2-chloroethyl methyl sulfide was primarily focused on probes to assess nucleophilic solvent assistance. The mustards used were often more involved structures meant to examine a particular topic regarding solvent assistance and not necessarily the hydrolysis itself.…”
Section: Introductionmentioning
confidence: 99%
“…Geminal dimethyl substitution is said to favor neighboring group participation by operation of the Thorpe-Ingold effect.4 Additionally with 2-OBs, the gem-dimethyl groups stabilize the product of methoxy group migration, i.e., Me2C+-CH2OMe. 3 The previous studies provide the basis for the present work which models the reactivity of simple polyethers like polyethylene glycol) (PEG) sulfonate esters. 5 In this report we have studied the polyether model substrate 3-OTs, which has the opportunity for both and RO-6 participation.…”
mentioning
confidence: 99%